Efficacy and Safety of Shufeng Jiedu Capsules in the Adjuvant Treatment of Community-acquired Pneumonia in Adult: a Meta-analysis - Jiang YANG, Xuanlin LI, Jianxin WANG, Yang XIE, Huiguo LIU, Suyun LI, Minghang WANG (Zhongguo quanke yixue, 2022)
Background Community-acquired pneumonia (CAP) is one of the common infectious diseases with high morbidity and heavy disease burden. Despite the continuous advancement of diagnostic technology and the launch of new antimicrobial drugs, the morbidity and mortality of CAP are still high. The clinical research of Shufeng Jiedu capsules in the adjuvant treatment of CAP is increasing, but there is still a lack of systematic review and meta-analysis. Objective To systematically evaluate the efficacy and safety of Shufeng Jiedu capsules in the treatment of CAP. Methods Randomized controlled trials (RCTs) about Shufeng Jiedu capsules in the treatment of CAP was retrieved in CNKI, Wanfang Data, VIP, SinoMed, PubMed, Cochrane Library and EMBase from inception to November 2021 by computer. The control group was treated with routine western medicine, and the experimental group was treated with Shufeng Jiedu capsules orally on the basis of the control group. The retrieval time was from the establishment of the database to November 2021. RevMan 5.3 software was used for data analysis, and GRADE criteria were used to evaluate the level of evidence for the outcome indicators. Results A total of 13 studies with 1 355 patients were included. The results of meta-analysis showed that the cure rate of the test group〔RR=1.49, 95%CI (1.28, 1.74), P<0.000 01〕, the total effective rate〔RR=1.18, 95%CI (1.13, 1.24), P<0.000 01〕, imaging complete absorption rate〔RR=1.57, 95%CI (1.13, 1.89), P<0.000 01〕 were higher than the control group, antibiotic use time〔MD=-1.25, 95%CI (-1.90, -0.61), P=0.000 1〕, time of fever disappearance〔MD=-1.15, 95%CI (-1.93, -0.37), P=0.004〕, time of cough disappearance〔MD=-0.96, 95%CI (-1.13, -0.80), P<0.000 01〕, time of expectoration disappearance〔MD=-1.44, 95%CI (-2.40, -0.48), P=0.003〕 and time of lung rales disappearance〔MD=-1.60, 95%CI (-2.33, -0.87), P<0.000 1〕 were shorter than the control group, C-reactive protein〔MD=-4.12, 95%CI (-6.95, -1.30), P=0.004〕 and white blood cell count〔MD=-2.20, 95%CI (-3.36, -1.05), P=0.000 2〕 were lower than the control group. There was no significant difference in the incidence of adverse events between the two groups〔RR=0.84, 95%CI (0.26, 2.67), P=0.76〕. The funnel chart of the cure rate showed that the left and right sides were asymmetrical, suggesting that there may be publication bias. GRADE grading results showed that the cure rate, total effective rate, the time of cough disappearance and imaging complete absorption rate were of moderate quality, the time of fever disappearance, expectoration disappearance and lung rales disappearance, C-reactive protein and white blood cell count were of low quality, the time of antibiotic use and the incidence of adverse events were of very low quality. Conclusion Shufeng Jiedu capsule has significant curative effect and good safety in the adjuvant treatment of CAP. However, due to the low quality of the included research methodology, more high-quality, multi-center and large sample trails are still needed for verification.